Insights on the Thermal Stability of the Sb2Se3 Quasi‐1D Photovoltaic Technology. Issue 10 (25th August 2021) - Vidal-Fuentes, Pedro; Guc, Maxim; Becerril-Romero, Ignacio; Sylla, Diouldé; Alcobé, Xavier; Sánchez, Yudania; Pérez-Rodríguez, Alejandro; Saucedo, Edgardo; Izquierdo-Roca, Victor
Abstract : This work explores the thermal stability of antimony‐based photovoltaic (PV) technologies investigating the effect of low‐temperature (50—350 °C) postdeposition annealings (PDAs) on bare Sb2 Se3 absorbers and complete SLG/Mo/Sb2 Se3 /CdS/i‐ZnO/ITO devices (5.7% power conversion efficiency with no anti‐reflecting coating or metallic grid). A comprehensive structural analysis by means of X‐ray diffraction and Raman spectroscopy, coupled with optoelectronic characterization, reveals clear evidences of a degradation process dominated by selenium diffusion. The degradation process is observed to start at low PDA temperatures as a shrinkage of the Sb2 Se3 unit cell. Further increasing the PDA temperature above 200 °C leads to the formation of Sb oxides and Se secondary phases in bare absorbers, and of CdS1— x Se x in complete devices at the Sb2 Se3 front interface which completely degrade the heterojunction and kill device performance. Furthermore, a clear correlation is found between PV performance decrease and Sb2 Se3 layer lattice shrinkage with the increasing PDA temperature ( T  > 50 °C). This is the first time that thermal instability is reported for the Sb2 Se3 compound at temperatures commonly used during PV module fabrication processes such as emitter/transparent conducting oxide deposition or encapsulation. Abstract : This work provides evidence on the thermal instability of the Sb2 Se3 photovoltaic technology under controlled low‐temperature (50—350 °C) postdeposition annealings. The degradation process starts as a shrinkage of the Sb2 Se3 unit cell. Higher temperatures (>200 °C) lead to the formation of SbO x and t‐Se secondary phases in bare absorbers and of CdS1— x Se x in complete devices degrading the heterojunction.